Modular design of trailers cranes - Nieoczym, Aleksander; Drozd, Kazimierz (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
A trailer crane is a device mounted on trailers intended for transporting timber. During the research and construction works, functional parameters of the cranes were defined. This enabled the development of five types of cranes differing in reach and capacity. In order to reduce the design and manufacturing costs, the main teams were divided into modules. Within each module, common parts have been separated, which can be used in the indicated types of cranes. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)